Silence as Leadership Communication: Public Perception, Interpretation, and Negotiated Meaning - Utulu, Anthony U.; Bello, David (European Scientific Journal, ESJ, 2023)
Every communication encounter primarily starts because initiators aim to inform and influence others. Silence is a form of nonverbal communication that can be deployed by those communicating. Since nonverbal communication complements the verbal form of communication, it is expected that it is effectively used to enhance the sender-receiver’s communication gains. This paper investigated leaders’ communication style and if leaders’ silence affected public perception, interpretation, and the meaning assigned to a communicated message, using the former Nigerian President, Muhammadu Buhari, and the Nigerian public as cases. It adopted a qualitative approach—an in-depth interview method, using an interview guide as the instrument for data collection. The data analyzed showed that adopting silence as a form of communication, especially during a crisis, would harm the human communication experience. Buhari’s silence toward Fulani herders’ attacks affected how the masses perceived, interpreted, and assigned meaning to his action. It allowed conspiracy theories to thrive as public opinion showed that his silence encouraged the herders’ nefarious actions.